Association between dietary inflammatory index and body fat percentage among newly diagnosed breast cancer patients - Ng, Wai Han; Abu Zaid, Zalina; Mohd Yusof, Barakatun Nisak; Amin Nordin, Syafinaz; Lim, Poh Ying (Taylor & Francis, 2023)
Background Obesity, particularly excessive body fat, is an established risk factor and substantial prognostic determinant in breast cancer. Recent studies suggested that diet-related inflammation plays a key role in obesity. This study aimed to determine the association between energy-adjusted dietary inflammatory index (E-DII) and body composition, particularly body fat percentage, among patients with newly diagnosed breast cancer. Materials and methods This cross-sectional study was conducted on 124 breast cancer outpatients within the first year of diagnosis and yet to commence oncological treatment. Body composition parameters [body weight, body mass index (BMI), body fat percentage, fat mass over fat-free mass ratio (FM/FFM), muscle mass, and visceral fat] were obtained using a bioelectrical impedance analyzer. Body fat percentage was categorized into two groups which were normal (<35%) and high (≥35%). The E-DII was calculated from the validated 165-items Food Frequency Questionnaire (FFQ) and categorized into three groups or tertiles. Multiple logistic regression analysis was used to determine the association between the E-DII and body fat percentage. Results Mean body weight, body fat percentage, FM/FFM, and visceral fat increased as E-DII increased from the lowest tertile (T1) to the most pro-inflammatory tertile (T3) (p for trend <0.05). E-DII was positively associated with body fat percentage (OR 2.952; 95% CI 1.154–7.556; p = 0.024) and remained significant after adjustment for cancer stage, age, physical activity, ethnicity, smoking history, and presence of comorbidities. Compared to T1, participants in T3 had a significantly lower consumption of fiber, vitamin A, beta-carotene, vitamin C, iron, thiamine, riboflavin, niacin, vitamin B6, folic acid, zinc, magnesium, and selenium, but a higher intake of total fat, saturated fat, and monounsaturated fatty acids. Conclusions A higher E-DII was associated with increased body fat percentage, suggesting the potential of advocating anti-inflammatory diet to combat obesity among newly diagnosed breast cancer patients.